Effect of heat treatment on magnetostructural transformations and exchange bias in Heusler Ni48Mn39.5Sn9.5Al3 ribbons. (15th January 2016) - Czaja, P.; Fitta, M.; Przewoźnik, J.; Maziarz, W.; Morgiel, J.; Czeppe, T.; Cesari, E.
Abstract: The influence of low temperature annealing and high temperature quenching on martensitic transformation, microstructure, magnetic and exchange bias properties of Ni48 Mn39.5 Sn9.5 Al3 metamagnetic shape memory alloy ribbons have been investigated. It is shown that with increasing thermal treatment temperature the martensitic transformation temperature increases and the exchange bias is reduced. In the case of low temperature annealing this effect is mediated by stress and structural relaxations, whereas in the case of high temperature annealing followed by water quenching this effect is ascribed to the combined influence of grain size enlargement and composition change resulting from metastability of the Ni–Mn–Sn–Al phase at elevated temperatures. Furthermore low temperature thermal treatment leads to the change in the martensite structure from 4O to 10M as is demonstrated by in situ TEM studies. It is demonstrated that low temperature annealing is a preferable method for fine tuning magnetostructural properties of Ni–Mn–Sn–Al ribbons. Graphical abstract: